2021
DOI: 10.1088/2058-9565/abee99
|View full text |Cite
|
Sign up to set email alerts
|

Motional heating of spatially extended ion crystals

Abstract: We study heating of motional modes of a single ion and of extended ion crystals trapped in a linear radio frequency (rf) Paul trap with a precision of Δ n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Experimentally reaching the required temperature regime close to the critical point could be achieved by preparing the system deeper in the pinned phase, where the mode frequency of the kink is high enough in order to allow for sufficient cooling while being energetically well isolated from the residual phonon spectrum [42]. In addition, studies have shown, that heating of short wavelength motional modes by dc electric field noise is strongly suppressed [44][45][46], such that effective cooling of the kink dynamics is possible. The kink in a crystal of 30 ions could be prepared at α − α A = 0.091 where the kink mode exhibits a frequency of 2π • 65.17 kHz at an axial trapping frequency of ω z = 2π • 150 kHz.…”
Section: Experimental Accessibilitymentioning
confidence: 99%
“…Experimentally reaching the required temperature regime close to the critical point could be achieved by preparing the system deeper in the pinned phase, where the mode frequency of the kink is high enough in order to allow for sufficient cooling while being energetically well isolated from the residual phonon spectrum [42]. In addition, studies have shown, that heating of short wavelength motional modes by dc electric field noise is strongly suppressed [44][45][46], such that effective cooling of the kink dynamics is possible. The kink in a crystal of 30 ions could be prepared at α − α A = 0.091 where the kink mode exhibits a frequency of 2π • 65.17 kHz at an axial trapping frequency of ω z = 2π • 150 kHz.…”
Section: Experimental Accessibilitymentioning
confidence: 99%
“…We show how to retrieve the modulation factor of the ion using a theoretical model to fit the spectra. We also estimate an effective temperature of the ion, evidencing the presence of an additional heating mechanism due to micromotion known as RF heating (Blümel et al, 1989;Kalincev et al, 2021). Moreover, we measure the spectra of more than one ion at the same time and retrieve the modulation factor of each ion through a fit to the model for the full measurement.…”
Section: Introductionmentioning
confidence: 99%